Preparation and characterization of polyaniline/sodium alginate-doped TiO2 nanoparticles with promising mechanical and electrical properties and antimicrobial activity for food packaging applications - Abutalib, M. M.; Rajeh, A. (Journal of materials science. Materials in electronics, 2020)
Polymer nanocomposite (PNC) films based on sodium alginate and polyaniline (SA/PANi) and TiO 2 as nanoceramic were synthesized by solution casting method. XRD displayed that the average size crystalline of the TiO 2 NPs is 19 nm, and the amorphuos degree of the SA/PANi blend decreased due to the addition of TiO 2 NPs. The interaction between the TiO 2 NPs and the SA/PANi blend was confirmed by FT-IR spectroscopy, due to vibrational changes that occurred after the addition of TiO 2 dopant in the polymer blend. The UV–Visible spectrum was used to calculate optical energy band gaps (direct and indirect). Both of the Eg di and Eg ind were reduced with the rise in TiO 2 content. Thermogravimetric showed that the thermal stability of the nanocomposite was higher than the pure SA/PANi. With the increase in TiO 2 NPs concentrations and frequency, the electrical properties such as dielectric and ac conductivity of pure blend improved and displayed maximum electrical properties (dielectric and conductivity) at 1 wt% loading. Additionally, the doping of TiO 2 NPs in the polymer matrix proved that the nanocomposites exhibited excellent antimicrobial activity against all the bacteria taken for the test. It is obvious from the results that the nanocomposites have the potential for use in active packaging applications.